The pains of being unauthorized in the Netherlands. (October 2020) - Kox, Mieke; Boone, Miranda; Staring, Richard
Ethnographic fieldwork amongst 105 unauthorized migrants in the Netherlands shows that unauthorized migrants suffer from the pains of being unauthorized. These migrants feel punished and are severely hurt by – amongst others – the deprivation of healthy and secure living conditions, social and geographical mobility and citizenship. These migrants' pains are caused by current restrictive migration controls, something the Dutch authorities could and should be aware of given previous research that provides similar insights. While the Dutch authorities do provide – the legally required – provisions for unauthorized migrants, we argue on the basis of Hayes' proximity model that these authorities accept the collateral consequences of (possibly) being subjected to migration controls and purposely inflict these pains on unauthorized migrants. This means that migration control is not only experienced as punishment by those subjected to it, but that it is also intended to punish. The current system of migration control has as such expanded the reach of penal power. This implies that 'punishment and society' scholarship should also look beyond the borders of nation-states and criminal laws in order to understand contemporary punishment.